SUPPLY CHAIN OPERATION REFERENCE ANALYSIS OF LOCAL VEGETABLE E-COMMERCE - Hamdani; Wahyudin; Nugraha, Billy (Jurnal Manajemen dan Agribisnis, 2021)
This study aims to determine the chain of sales of vegetables in Teluk Jambe, Karawang Regency. In addition, it can cut off the chain of sales from farmers to consumers. While the scope of this study only discusses the vegetables only. This research type is descriptive qualitative and done with the concept of qualitative descriptive. Descriptive qualitative is the concept of research with the process of obtaining data that is potluck. Analyze the supply chain of vegetables commercial with the methods of Supply Chain Operation Reference (SCOR). The results of the study showed the presence of Sis-Log In Apps could be cut chain sales. So from the results of this study provide a positive impact for farmers. In conclusion, Sis-Log In Apps is designed to cut the chain of sale of commodity vegetables only. With the results as a liaison and direct intermediaries between farmers and consumers. Keywords: Agriculture, e-commerce, SCM, SCOR, Sis-Log In Apps